Draft Genome Sequence for the Tree Pathogen Phytophthora plurivora. (30th July 2018) - Vetukuri, Ramesh R; Tripathy, Sucheta; Malar C, Mathu; Panda, Arijit; Kushwaha, Sandeep K; Chawade, Aakash; Andreasson, Erik; Grenville-Briggs, Laura J; Whisson, Stephen C
Abstract: Species from the genus Phytophthora are well represented among organisms causing serious diseases on trees. Phytophthora plurivora has been implicated in long-term decline of woodland trees across Europe. Here we present a draft genome sequence of P. plurivora, originally isolated from diseased European beech ( Fagus sylvatica ) in Malmö, Sweden. When compared with other sequenced Phytophthora species, the P. plurivora genome assembly is relatively compact, spanning 41 Mb. This is organized in 1, 919 contigs and 1, 898 scaffolds, encompassing 11, 741 predicted genes, and has a repeat content of approximately 15%. Comparison of allele frequencies revealed evidence for tetraploidy in the sequenced isolate. As in other sequenced Phytophthora species, P. plurivora possesses genes for pathogenicity-associated RXLR and Crinkle and Necrosis effectors, predominantly located in gene-sparse genomic regions. Comparison of the P. plurivora RXLR effectors with orthologs in other sequenced species in the same clade ( Phytophthora multivora and Phytophthora capsici ) revealed that the orthologs were likely to be under neutral or purifying selection.